2018
DOI: 10.1108/rsr-09-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Chatting while you work

Abstract: Purpose To understand chat reference user needs at the University of Arizona Libraries, this study aims to analyze the differences in READ (Reference Effort Assessment Data) scores and content from two different chat reference origins: the library website and, course sites within the campus course management system, Desire2Learn. Design/methodology/approach The authors have used a mixed methods approach, whereby ordinal regression has been performed on READ scores and grounded theory on chat transcripts in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Larson et al (2014) highlighted consistent application of the scale as an issue when a chat service employed both local and consortial chat agents. However, the rest of the articles did not have any crossinstitution norming, though five (in addition to Gerlich and Berard), performed some form of inter-rater norming for their own data (Belanger et al, 2016;Kemp et al, 2015;Keyes & Dworak, 2017;Stieve & Wallace, 2018). In the remainder, no mention was made of any norming of READ Scale ratings, other than Warner et al (2020) who explicitly stated that interrater reliability was not tested as part of the study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Larson et al (2014) highlighted consistent application of the scale as an issue when a chat service employed both local and consortial chat agents. However, the rest of the articles did not have any crossinstitution norming, though five (in addition to Gerlich and Berard), performed some form of inter-rater norming for their own data (Belanger et al, 2016;Kemp et al, 2015;Keyes & Dworak, 2017;Stieve & Wallace, 2018). In the remainder, no mention was made of any norming of READ Scale ratings, other than Warner et al (2020) who explicitly stated that interrater reliability was not tested as part of the study.…”
Section: Resultsmentioning
confidence: 99%
“…While the READ Scale is a 6-point scale, the 1-4 range of the scale was heavily used, while the 5-6 range was not. Belanger et al (2016), Gerlich andBerard, (2010), Kohler (2017), Stieve and Wallace (2018), and Ward and Jacoby (2018) found that zero chats were rated a 5 or 6. Kayongo andVan Jacob (2011), Cabaniss (2015), and Mavodza (2019) found that the majority of chat interactions fell within the 1-3 range.…”
Section: The Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles reporting the results of research on digital reference including chat have been published since the 1990s (Matteson et al , 2011). Topics covered in the last few years of literature have ranged from teaching or instruction in chat (Dempsey, 2016, 2017; Hervieux and Tummon, 2018; Jacoby et al , 2016; Schiller, 2016), the types of questions asked in a chat service (Bourgeois and Bealer, 2020; Brown, 2017; Chen and Wang, 2019; Mavodza, 2019; McKewan and Richmond, 2017; Ozeran and Martin, 2019; Stieve and Wallace, 2018), staffing hours or needs, patron satisfaction with the service (Brown, 2017; Mungin, 2017), the role of cobrowsing (Wan et al , 2009) and communication issues (Westbrook, 2007). Probably the largest and most prolific area has involved service quality.…”
Section: Literature Reviewmentioning
confidence: 99%